2007
DOI: 10.1021/pr060629m
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Secreted Biomarkers Using LC-MS/MS in Isogenic Cell Lines Representing a Progression of Breast Cancer

Abstract: Proteins secreted (the secretome) from cancer cells are potentially useful as biomarkers of the disease. Using LC-MS/MS, the secreted proteomes from a series of isogenic breast cancer cell lines varying in aggressiveness were analyzed by mass spectrometry: non-tumorigenic MCF10A, premalignant/ tumorigenic MCF10AT, tumorigenic/locally invasive MCF10 DCIS.com and tumorigenic/ metastatic MCF 10CA cl. D. Proteomes were obtained from conditioned serum-free media, partially fractionated using a small reverse phase C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(122 citation statements)
references
References 73 publications
(134 reference statements)
1
119
1
Order By: Relevance
“…S100B is actively secreted by cells, and previous studies have shown the effect of extracellular S100B on cellular functions. S100A6 was found in the extracellular medium of breast cancer cells (13), but to our knowledge, no data are available on the active secretion of S100A6 by cells and on the extracellular effect of the protein on cellular functions. To determine whether S100A6 was actively released from brain-related cells, we used human U87-MG glioblastoma cells, which endogenously express S100A6 ( Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…S100B is actively secreted by cells, and previous studies have shown the effect of extracellular S100B on cellular functions. S100A6 was found in the extracellular medium of breast cancer cells (13), but to our knowledge, no data are available on the active secretion of S100A6 by cells and on the extracellular effect of the protein on cellular functions. To determine whether S100A6 was actively released from brain-related cells, we used human U87-MG glioblastoma cells, which endogenously express S100A6 ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Similarly S100A12 is found in synovial fluid of patients suffering from rheumatoid arthritis and also triggers neuritogenesis of hippocampal neurons when added extracellularly at submicromolar to micromolar concentrations (11,12). Finally S100A6 was found in the extracellular medium of breast cancer cells (13). S100B is mainly expressed in the brain and primarily in astrocytes of the human cortex and hippocampus but is also present in certain populations of oligodendrocytes and neurons (14 -18).…”
mentioning
confidence: 99%
“…The first breast cancer metastasis secretome study profiled the secretomes of the MCF10A metastasis progression series, finding proteins such as alpha-1-antichymotrypsin and galectin-3-binding protein to be upregulated in conditioned media from the metastatic variants [48]. More recently, many secretome analyses of cell lines representing several different cancer types have been reported [8,[30][31][32][33][34][35][36][37][38][39][40].…”
Section: Mario Andres Blanco Et Al 1349mentioning
confidence: 99%
“…To observe changes in the secreted protein profiles of melanoma samples following PAEP-silencing, mass spectral analysis was conducted on a Thermo Fisher Orbitrap mass spectrometer (Thermo Fisher, Waltham, MA, USA) with an Agilent 1200 Series Nanoflow LC (Agilent Technologies, Santa Clara, CA, USA) for sample introduction, as previously described (13)(14)(15). Prior to analysis, secreted proteins isolated from PAEP-knockdown and non-targeting knockdown 624.38-Mel cells were digested with trypsin in the presence of a reducing agent.…”
Section: Western Blot Analysismentioning
confidence: 99%